Progress on the national action plan of Pakistan on antimicrobial resistance (AMR): a narrative review and the implications. Issue 1 (2nd January 2022) - Saleem, Zikria; Godman, Brian; Azhar, Faiza; Kalungia, Aubrey C.; Fadare, Joseph; Opanga, Sylvia; Markovic-Pekovic, Vanda; Hoxha, Iris; Saeed, Amna; Al-Gethamy, Manal; Haseeb, Abdul; Salman, Muhammad; et al.
ABSTRACT: Introduction: The emergence of antimicrobial resistance (AMR) is a threat to public health. In 2015, the World Health Organization (WHO) introduced a global action plan to tackle AMR in the World Health Assembly. Pakistan's national action plan (NAP) for AMR was released in May 2017 by the Ministry of National Health Services. Based on the NAP, strategies have been initiated on a national and provincial scale in Pakistan. Areas covered: This narrative review of the five components of the Pakistan NAP has been undertaken to discuss some of the challenges in implementation of the NAP for AMR in Pakistan including different opinions and views of key stakeholders, combined with suggestions on potential ways to reduce the burden of the AMR. Expert opinion: Going forward, healthcare authorities should focus on screening and monitoring of all the objectives of the NAP by establishing proper policies as well as promoting antimicrobial stewardship interventions and Infection prevention and control (IPC) practices. Overall, the comprehensive strengthening of the healthcare system is required to adequately implement the NAP, tackle continued inappropriate antimicrobial use and high AMR rates in Pakistan.